“Rêrag pragtag”: A sociophonetic exploration of the vowel quality of the -ig suffix in Kaaps - Ribbens-Klein, Yolandi (Stellenbosch Papers in Linguistics Plus, 2023)
In this squib, I propose a sociophonetic exploration into the vowel quality of the adjectivising and pseudo suffix -ig (spelled as <ig> or <ag>) in the language variety called Kaaps. This investigation not only falls within the ambit of the phenomenon of vowel-lowering in Afrikaans and Kaaps, but also aims to motivate further research on the acoustics of schwa /ə/ in Afrikaans and Kaaps. I start out by briefly contextualising Kaaps as a social, ethno-regional linguistic entity that is indexical of not only place, but also involves identity politics related to experiences of marginalisation and self-affirmation. Next, I distinguish between adjectivising and pseudo suffixes, before discussing previous research on Afrikaans and Kaaps schwa and vowellowering. Comparing older phonetic texts to current research shows that while variation in schwa realisation was widespread in the early twentieth century, lowered schwa gradually became metapragmatically associated with present-day Kaaps. Finally, I propose further research directions that will seek to explore sociolinguistic, phonetic, and phonological processes involved in schwa realisation in the -ig suffix (henceforth referred to as the -ig vowel). The realisations of the -ig vowel can move us towards further exploration of Lass’ (1986, 2007) claims that there is more to schwa than meets the transcriber’s eye; it is possible that sounds transcribed as schwa are, in fact, cases where the eye is favoured instead of the ear. The spelling of the -ig vowel as <ag> in Kaaps points us in that direction.